2006
DOI: 10.1038/msb4100063
|View full text |Cite
|
Sign up to set email alerts
|

Residues crucial for maintaining short paths in network communication mediate signaling in proteins

Abstract: Here, we represent protein structures as residue interacting networks, which are assumed to involve a permanent flow of information between amino acids. By removal of nodes from the protein network, we identify fold centrally conserved residues, which are crucial for sustaining the shortest pathways and thus play key roles in long-range interactions. Analysis of seven protein families (myoglobins, G-protein-coupled receptors, the trypsin class of serine proteases, hemoglobins, oligosaccharide phosphorylases, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
286
0
8

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(306 citation statements)
references
References 59 publications
11
286
0
8
Order By: Relevance
“…The more rigid protein core residues are not identified in the allosteric maps at this level of coarse-graining, indicating that multiscale modeling may be needed to identify those residues. The theoretically identified allosteric sites are also consistent with the sequence-based analysis of Ranganathan et al (36) [residues 113, 293-295, 299, and 302 (301 in our analysis)] and with the topology-based analysis of Nussinov et al (38) (residues 67, 301, and 312). Although the predictions of the different models are not identical, they are consistent and successful in capturing the key allosteric sites, including the ligand environment and the G-protein binding site.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The more rigid protein core residues are not identified in the allosteric maps at this level of coarse-graining, indicating that multiscale modeling may be needed to identify those residues. The theoretically identified allosteric sites are also consistent with the sequence-based analysis of Ranganathan et al (36) [residues 113, 293-295, 299, and 302 (301 in our analysis)] and with the topology-based analysis of Nussinov et al (38) (residues 67, 301, and 312). Although the predictions of the different models are not identical, they are consistent and successful in capturing the key allosteric sites, including the ligand environment and the G-protein binding site.…”
Section: Resultssupporting
confidence: 77%
“…Allosteric Sites. The allosteric sites predicted from our model, from bioinformatics analysis of conserved residues (36,38), and obtained in experiments (21) are shown in Fig. 2 E and F. In rhodopsin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of each residue or node to the characteristic path length (CPL), defined as an average of the shortest path length between all pairs of nodes in the network, provides an estimate of the effect of node connectivity on communication pathways in a protein. Conserved residues that greatly affect the CPL upon removal have been hypothesized to be important for allosteric signal transmission (10). Snapshots from a short simulation of a modeled MetRS:tRNA complex indicated that the shortest path between protein residues interacting with the anticodon and the adenylate binding site was sensitive to conformational changes in the protein (11), but the tRNA and contacts with other identity elements on the tRNA were neglected in their study of the signal transmission.…”
mentioning
confidence: 99%
“…In fact, there have been several statistical modelings of individual proteins as networks (Amitai et al, 2004;del Sol et al, 2006;del Sol and O'Meara, 2005;Greene and Higman, 2003). Also, for allosteric changes in a protein to occur, residues involved in the allosteric pathway within each protein subunit are predicted to be energetically coupled and evolutionarily co-evolving (Lockless and Ranganathan, 1999).…”
Section: Physical Evidence Of Allosteric Pathways In Individual Proteinsmentioning
confidence: 99%